The complete mitogenome of Haliotis asinina (Gastropoda, Haliotidae) from Malaysian waters provides further insights into the phylogeny of the abalone - Nur‐Syahirah Mamat; Yuzine Esa; Nur Leena W. S. Wong; Siti‐Azizah Mohd Nor; Nazia Abdul Kadar; Julia D. Sigwart; Aziz Arshad (New Zealand Journal of Marine and Freshwater Research, 2025)
Due to its high economic importance, the aquaculture of abalone has developed significantly as a global industry. However, there is still limited studies of abalone in Malaysia. Therefore, the complete mitochondrial genome of the tropical abalone, Haliotis asinina (Linnaeus 1758) sampled in the Malaysian waters is sequenced and analysed for the first time. The mitogenome is 16399 base pairs (bp) in length and contains 13 protein coding genes (PCGs), 2 ribosomal RNA (rRNA) genes and 22 transfer RNA (tRNA) genes. The arrangement and orientation of genes compared with 10 available Haliotis mitogenomes were found to be identical. Phylogenetic analysis was conducted to assess their evolutionary relationships. The phylogenetic tree shows that H. asinina is closely related to H. ovina, H. diversicolor, H. varia, H. rubra and H. tuberculata. The genetic information gleaned from this study will be invaluable for the further studies of H. asinina especially on population genetics and improvement of aquaculture in the face of climate change effects.

Quorum sensing signals: Aquaculture risk factor - P. Snega Priya; Seenivasan Boopathi; Raghul Murugan; B. Haridevamuthu; Aziz Arshad; Jesu Arockiaraj (Reviews in Aquaculture, 2023)
Bacteria produce several virulence factors and cause massive mortality in fish and crustaceans. Abundant quorum sensing (QS) signals and high cell density are essentially required for the production of such virulence factors. Although several strategies have been developed to control aquatic pathogens through antibiotics and QS inhibition, the impact of pre‐existing QS signals in the aquatic environment has been overlooked. QS signals cause detrimental effects on mammalian cells and induce cell death by interfering with multiple cellular pathways. Moreover, QS signals not only function as a messenger, but also annihilate the functions of the host immune system which implies that QS signals should be designated as a major virulence factor. Despite QS signals' role has been well documented in mammalian cells, their impact on aquatic organisms is still at the budding stage. However, many aquatic organisms produce enzymes that degrade and detoxify such QS signals. In addition, physical and chemical factors also determine the stability of the QS signals in the aqueous environment. The balance between QS signals and existing QS signals degrading factors essentially determines the disease progression in aquatic organisms. In this review, we highlight the impact of QS signals on aquatic organisms and further discussed potential alternative strategies to control disease progression.

Long non‐coding RNA , a supreme post‐transcriptional immune regulator of bacterial or virus‐driven immune evolution in teleost - B. Haridevamuthu; Ajay Guru; Manikandan Velayutham; P. Snega Priya; Aziz Arshad; Jesu Arockiaraj (Reviews in Aquaculture, 2023)
The global aquaculture boom, fuelled by a reduction in wild population and detection of novel viruses, has created a demanding market, hence, there is a pressing need to investigate the immune system of fish, further. As the most diverse community of vertebrates and a central contributor to the progressing global aquaculture market, teleost continues to draw vast scientific interest. Recent breakthroughs in multi‐omics technologies have provided a platform to understand the role of long non‐coding RNA (lncRNA) in the host immune system during infection. Emerging evidence shows that teleost lncRNA might have a regulatory role in immune responses, mostly through lncRNA–microRNA (miRNA) sponging. Teleost lncRNA shares a functionally active short sequence complement to target the miRNA which is conserved among the several fish species. Recent report suggests that rhabdovirus exploits a lncRNA in teleost and, to dodge the host immune mechanism and negatively regulate the immune system. This observation reveals the essentiality of lncRNA in pathogen‐driven immunity in teleost. Reports available on the function of teleost lncRNA are still in early stages and experimental verifications are a limiting factor. Unravelling the lncRNA‐mediated immune regulation in fishes could be used against the invading pathogens to strengthen the aquaculture production. This review elaborates on the experimentally identified and functionally characterized lncRNA and its regulatory role in the teleost immune response during infection and pathogen‐driven host immune evolution, which could eventually lead to achieving high standards in aquaculture productivity.

Double‐edged sword role of shrimp miRNA explains an evolutionary language between shrimp‐pathogen interactions that unties the knot of shrimp infection - Hari Deva Muthu B; Ajay Guru; Gokul Sudhakaran; Raghul Murugan; Aziz Arshad; Jesu Arockiaraj (Reviews in Aquaculture, 2022)
Shrimp production, using a small‐scale enclosed pond system, is a rapidly growing aquaculture sector, which is valued around USD 18.30 billion in 2020. Intensified shrimp culture leads to the outbreak of transmissible diseases to eventually cause a huge loss in the production process and thus the economy. Studies on microRNA (miRNA) reveal that miRNA has an influential role in the host‐pathogen interaction during an infection. Recently, shrimp miRNA has been shown to help pathogen‐like viruses for their replication and infection. Several shrimp miRNAs were reported to be involved in enhancing host immunity against viral infection, especially white spot syndrome virus (WSSV) infection and Vibrio infection caused by bacterial species, whereas some shrimp miRNAs were reported to be hijacked by WSSV and to enhance the viral replication and establish the infection in shrimp. This gives an insight into the double‐edged sword role played by shrimp miRNA during host‐pathogen interaction. In future, this role could be employed against the virus to strengthen the shrimp culture. In this review, we discuss the role of shrimp miRNA and their mechanism(s) associated with the establishment of host‐pathogen interaction during infection, which will reveal the complexity associated with shrimp infection.

Functional role of piRNAs in animal models and its prospects in aquaculture - Christy Lite; Vasisht Varsh Sridhar; Swati Sriram; Melita Juliet; Aziz Arshad; Jesu Arockiaraj (Reviews in Aquaculture, 2021)
The recent advances in the field of aquaculture over the last decade has helped the cultured‐fish industry production sector to identify problems and choose the best approaches to achieve high‐volume production. Understanding the emerging roles of non‐coding RNA (ncRNA) in the regulation of fish physiology and health will assist in gaining knowledge on the possible applications of ncRNAs for the advancement of aquaculture. There is information available on the practical considerations of epigenetic mechanisms like DNA methylation, histone modification and ncRNAs, such as microRNA in aquaculture, for both fish and shellfish. Among the non‐coding RNAs, PIWI‐interacting RNA (piRNA) is 24–31 bp long transcripts, which is primarily involved in silencing the germline transposons. Besides, the burgeoning reports and studies establish piRNAs' role in various aspects of biology. Till date, there are no reviews that summarize the recent findings available on piRNAs in animal models, especially on piRNAs biogenesis and biological action. To gain a better understanding and get an overview on the process of piRNA genesis among the different animals, this work reviews the literature available on the processes of piRNA biogenesis in animal models with special reference to aquatic animal model zebrafish. This review also presents a short discussion and prospects of piRNA’s application in relevance to the aquaculture industry.

Gut microbiota metagenomics in aquaculture: factors influencing gut microbiome and its physiological role in fish - Kumarasan Yukgehnaish; Praveen Kumar; Parimannan Sivachandran; Kasi Marimuthu; Aziz Arshad; Bilal Ahmad Paray; Jesu Arockiaraj (Reviews in Aquaculture, 2020)
Fish gut microbiome confers various effects to the host fish; this includes overall size, metabolism, feeding behaviour and immune response in the fish. The emergence of antimicrobial‐resistant (AMR) bacteria and hard to cure fish diseases warrant the possible utilization of gut microbes that exhibits a positive effect on the fish and thus lead to the usage of these microbes as probiotics. The widespread and systematic use of antibiotics has led to severe biological and ecological problems, especially the development of antibiotic resistance that affects the gut microbiota of aquatic organisms. Probiotics are proposed as an effective and environmentally friendly alternative to antibiotics, known as beneficial microbes. At the same time, prebiotics are considered beneficial to the host's health and growth by decreasing the prevalence of intestinal pathogens and/or changing the development of bacterial metabolites related to health. Uprise of sequencing technology and the development of intricate bioinformatics tools has provided a way to study these gut microbes through metagenomic analysis. From various metagenomic studies, ample of information was obtained; such information includes the effect of the gut microbiome on the physiology of fish, gut microbe composition of different fish, factors affecting the gut microbial composition of the fish and the immunological effect of gut microbes in fish; such this information related to the fish gut microbiome, their function and their importance in aquaculture is discussed in this review.